Becoming new together: making meaning with newcomers through an arts-based ethnographic research design. Issue 2 (2nd April 2020) - Kassan, Anusha; Goopy, Suzanne; Green, Amy; Arthur, Nancy; Nutter, Sarah; Russell-Mayhew, Shelly; Vazquez, Monica Sesma; Silversides, Halley
ABSTRACT: This article proposes an arts-based ethnographic research design as a means of engaging in ethical, meaningful, and culturally sensitive research with newcomer communities. Moving away from the manner in which culture has traditionally been defined and studied in psychology, this research design uses cultural probes and subsequent qualitative interviews to collect data about newcomers' everyday experiences in Canada. Cultural probes are sets of creative items (e.g., cameras, diaries, maps, paint supplies, postcards) that are given to participants to prompt them to document their lives in their new environment. These cultural probes are later unpacked and discussed in individual qualitative interviews. Results are disseminated and archived in ways that are meant to engage and empower communities. Specifically, the process of creating a cultural exhibit collaboratively with participants is discussed.